2021
DOI: 10.3389/fcell.2021.712224
|View full text |Cite
|
Sign up to set email alerts
|

ESRRB Facilitates the Conversion of Trophoblast-Like Stem Cells From Induced Pluripotent Stem Cells by Directly Regulating CDX2

Abstract: Porcine-induced pluripotent stem cells (piPSCs) could serve as a great model system for human stem cell preclinical research. However, the pluripotency gene network of piPSCs, especially the function for the core transcription factor estrogen-related receptor beta (ESRRB), was poorly understood. Here, we constructed ESRRB-overexpressing piPSCs (ESRRB-piPSCs). Compared with the control piPSCs (CON-piPSCs), the ESRRB-piPSCs showed flat, monolayered colony morphology. Moreover, the ESRRB-piPSCs showed greater chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Another huge drawback of the present piPSCs is that it was still hard to contribute to efficient chimeras and was extremely sensitive to perturbation in culture conditions. Previous studies showed that overexpression of BCL2 enhanced piPSCs’ survival under stress and contributed to chimera formation, and this effect was mediated mainly by the increased resistance to apoptosis [ 28 , 29 , 30 ]. In our study, we also confirmed that the caspase family CASPASE3 , CASPASE9 , and apoptotic protein BAX were down-regulated after AXIN2 knockdown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another huge drawback of the present piPSCs is that it was still hard to contribute to efficient chimeras and was extremely sensitive to perturbation in culture conditions. Previous studies showed that overexpression of BCL2 enhanced piPSCs’ survival under stress and contributed to chimera formation, and this effect was mediated mainly by the increased resistance to apoptosis [ 28 , 29 , 30 ]. In our study, we also confirmed that the caspase family CASPASE3 , CASPASE9 , and apoptotic protein BAX were down-regulated after AXIN2 knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the function of AXIN, the genes, AXIN1 and AXIN2, were PCR-amplified from piPSCs and then were subcloned into EF1-3FLAG-MCS-T2A-puromycin Lentiviral vectors [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…In our recent study, we found that ESRRB could trigger piPSC differentiation into TLSCs through activating CDX2 and KRT8 expression [ 5 ]. However, the mechanisms of histone modifications underlying the conversion process are yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Io et al established an in vitro model of the trophoblast lineage from human iPSCs [ 4 ]. We also found that Estrogen-Related Receptor Beta (ESRRB) overexpression in pig iPSCs (piPSCs) could cause the trans-differentiation of piPSCs into TLSCs [ 5 ]. This result reflects the powerful function of the transcription factor ESRRB.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of the iPSC inducing factors OCT-4 , SOX2 , KLF4 and c-MYC (OSKM) in porcine cells prior to nuclear transfer improved blastocyst rates and quality of SCNT embryos ( Song Z. et al, 2014 ; Kim et al, 2019 ). The co-expression of OKSM and the estrogen-related receptor B ( ESRRB ), which is abundantly expressed in pig embryos ( Yu et al, 2021 ), improved iPSCs production by regulating pluripotency factors ( Shi et al, 2020 ). In addition, pig iPSCs overexpressing ESRRB showed higher potential for trophectoderm differentiation when injected into 8-cell stage embryos ( Yu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%